Teaching Them Early: Formal Methods in School - Faron Moller (International Workshop on Formal Methods - Fun for Everybody FMFun 2019: Formal Methods – Fun for Everybody, 2021)
In this paper, we describe a programme of school engagement aimed at instilling a discipline of computational thinking within pupils before they embark on a university course. The workshops we deliver are designed mainly to increase the pipeline of school leavers going on to study computer science or software engineering, specifically by changing perceptions on what this means amongst the vast majority – particularly girls – who think it is just a geeky topic for boys.Over the past number of years, student enrollment has been increasing dramatically in our university’s undergraduate computer science and software engineering degree programmes. Also, the performance of the students on first-year formal methods modules – which has historically been poor – has risen substantially. Whilst there are many influences contributing towards these trends, we present evidence that our efforts with school engagement has to a non-trivial extent contributed towards these: both through the way the undergraduate programme has been adapted to incorporate the Technocamps approach, and through providing a pipeline of students who understand the principles of computational thinking.